The Game "Inside Me": Designing a Game for Evaluation and Feasibility Study of Effects of Video Games on Anger and How to Control it: A Causal-Comparative Study - Abbas Mousivand; Mahdi Pourjafar; Shahriyar Derhami; Yazdan Movahedi (Vesnu Publications, 2020)
Introduction: In this study, a user interface was designed based on anger management to create a medium by access to which the user may control or decrease his/her anger against the individual causing the anger. The tools and audio-visual effects presented in the game were devised to release furious emotions of the user and in certain states, to examine the result of provocation of anger in the user. This study aims to investigate the impact of video game on anger management and control against a particular person. Materials and Methods: This study involved the two experimental and control groups with the subjects selected from students of Tabriz Islamic Art University, Iran. 10 students were selected and assigned to the two groups (5 in each group). The experimental group received the game, but the control group did not receive it. The final data was analyzed using the univariate analysis of covariance (ANCOVA). Results: Based on the data analysis, there was a significant difference in the mean scores in the pretest and posttest stages for the experimental and control group, (P = 0.050), so that the game led to some development in anger management towards a special person. Conclusion: Overall, this study showed that "Inside Me" game can be used as an effective method to improve the ability of prevention of anger towards a certain person.